Latihan Pembinaan Imam Masjid Paripurna Kota Pekanbaru - Muhamamd Ashsubli; Robithoh Alamhadi Faisal (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Community service is an integral part of the Tri Dharma of Higher Education, aimed at providing tangible contributions to society. This activity was carried out in the form of a training program for the development of paripurna mosque imams across Pekanbaru City, focusing on improving the competencies of imams in both religious practices and the understanding of Islamic economics. The background of this activity is based on the existing gaps in imam quality, the lack of integrated training programs, and the increasing demands placed on the role of imams in society. The methods used in this program included observation, interviews, and the implementation of direct training sessions in mosques. The results of the activity indicate an improvement in participants’ understanding of the strategic role of imams as well as their literacy in Islamic economics. In addition, this program also strengthened the role of mosques as centers of worship, education, social engagement, and community-based economic development.This activity is expected to serve as an initial step toward developing professional, ethical, and competent mosque imams who are capable of addressing the challenges of modern society.